PENGARUH LINGKUNGAN SOSIAL DAN RELIGIUSITAS TERHADAP KEPUTUSAN MEMILIH PERBANKAN SYARIAH DI LUMAJANG - Nadya Salsabila; Vietha Devia (Islamic Economics and finance in Focus, 2024)
This research aims to determine the influence that occurs partially on the social environment (X1) and religiosity (X2) on the decision to choose sharia banking (Y) in the people of Lumajang Regency using quantitative methods with the research tool used is multiple linear regression analysis. The data collected is primary data. This research uses a Likert scale questionnaire instrument. A total of 120 respondents were obtained using purposive sampling technique. The results show that both the social environment and religiosity each have a partial positive effect on the decision to use sharia banking. From the results obtained, the advice that the author can give is that sharia banking in Lumajang Regency is expected to be able to continue to optimize, improve and improve products and services in accordance with the principles and teachings of the Islamic religion so that sharia banking which is in line with the local values of the Lumajang community can continue experience good development in the future.